PENGEMBANGAN MODUL AJAR UNTUK MEMBANTU PEMBELAJARAN BERDIFERENSIASI PADA MATERI GELOMBANG BUNYI - Firliana Sani; M. Barkah Salim; Dedy Hidayatullah Alarifin (Universitas Muhammadiyah Metro, 2024)
Differentiated teaching modules are designed to provide learningexperiences that are more appropriate to students' learning styles and focus onstudent-centered learning. Therefore, students with different interests andtalents can obtain learning material in the same class but in different ways, oneof which can be identified by looking at the learning style of each student. Theaim of this research is to determine the level of feasibility and user response toteaching modules to assist differentiated learning in sound wave material. Thistype of research is descriptive quantitative with the development model used isADDIE, which involves five stages: Analysis, Design, Development,Implementation, and Evaluation. The instruments used were interview sheetsand assessment questionnaires in the form of validation from media experts,material experts, summative tests and user responses. Researchers used theresults of assessment questionnaires and interviews to make it easier to drawconclusions. Based on the analysis results, the average percentage value ofthe three validations is 86.2%. The teaching module developed is very worthyof the valid category. The results of responses from users of the teachingmodule for learning differentiation of sound wave material from physics subjecteducators at SMA Negeri 1 Batanghari, SMA Negeri 1 Metro, and MAMuhammadiyah Metro obtained an average percentage score of 88.1% with thecriteria